Kinetika reaksi oksidasi pirit dalam larutan feri khlorida pada reaktor tangki berpengaduk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Rock mining residue and peat soil containing pyrite can produce acid waste that cause environmental pollution. Oxidation of pyrite in aqueous ferric chloride is one of the method used to reduce acid waste. Reaction kinetics data are needed to design a reactor. The objective of this research was to study the kinetics and the effect of the various variables affecting the oxidation of pyrite in ferric chloride solution. The process was carried out in semi batch stirred tank reactor. The variables studied were temperature, molar ratio offerric chloride pyrite, and the size of particle. Experiment was carried out at a certain time and samples were taken periodically and analyzed for their sulfate, ferro and total iron concentrations. The results showed that the reaction kinetics could be approached itith a combination of the liquid-gas model: reaction of ferro chloride and oxygen and the solid-liquid reaction model: reaction of pyrite and ferric chloride according to Shrinking Core Model. Reaction kinetics was controlled by chemical reaction and the formation of ferric chloride was the controlling step. The effect of temperature could be expressed by Arrhenius equation with activation energy for pyrite and ferric chloride reaction, EI of 9811.258 cal/mole and for ferro chloride and oxygen reaction, E2 of 4995.278 cal/ mole. Mole ratio offerric chloride-pyrite and solid particle size affected the rate constants logarithmically. The effect of temperature, mole ratio offerric chloride-pyrite and solid particle size on lcl and k2 could be presented as: ki = 152.436e (-9697.004 RT) m 0.504 Rb â0.146 ,cm/men it k2 = 23I2.865e(-5116.9141 RT) ,(cm3/mmol)2/menit under the process condition of 313 to 343 K, M = 8 to 24, Rb = 2.025x10-3 to 1.058x10-2 cm.